TÜRKİYE’DE SOSYAL MEDYA ÜZERİNDEN SİYASAL PROPAGANDA YAPMAK: 2018 CUMHURBAŞKANI SEÇİMİ ÖRNEĞİ - SÜTCÜ, CEM SEFA (My University, 2019)
Siyasal propaganda, seçmenlerin tutum ve davranışlarını etkilemeyi amaçlayan iletişim ve etkileşim faaliyetleridir. Sosyal medya, çift yönlü iletişim ve etkileşime imkân sağlayan bir ortam olması nedeniyle son yıllarda siyasal propaganda için yeni fırsatlar sunmaktadır. Özellikle zamanının büyük bölümünü internette geçiren ve “dijital yerli” şeklinde isimlendirilen seçmen grubuna ulaşmaya imkân sağlayan sosyal medya yaklaşık son on yıldır siyasal partiler ve siyasetçiler tarafından propaganda amaçlı kullanılmaktadır. Türkiye’de ise siyasetçilerin sosyal medyaya olan ilgilerinin giderek arttığı bir süreçte seçilme yaşının da 18’e indirilmesiyle birlikte sosyal medyanın siyasal propaganda için kullanılacak temel araçlardan biri olacağı söylenebilir. Bu çalışmada, 24 Haziran 2018 tarihinde gerçekleştirilen Cumhurbaşkanı seçiminde aday olan siyasetçilerin Twitter hesapları ve paylaşımları içerik analizi yöntemiyle incelenmiştir. Adayların, yaptıkları paylaşımlar sonucunda takipçi sayılarının üzerinde oldukça yüksek etkileşim sayılarına ulaşmış olmaları, kendi seçmenlerinden çok daha geniş kitlelere mesajlarını iletebildiklerini göstermektedir. Bu bakımdan, doğrudan oy verme şeklinde olmasa da sempati kazanma, itibar ve algı yönetimi konularında Twitter’ın adaylara avantaj sağladığını söylemek mümkündür. Twitter kullanım oranının artmasına ve Twitter kullanıcılarının demografik özelliklerinin tüm Türkiye’yi temsil edecek bir yapıya ulaşmasına bağlı olarak, ilerleyen yıllarda yapılacak seçimlerde Twitter’ın gerek seçmen tutumları gerekse oy verme davranışları üzerinde çok daha etkili olabileceği değerlendirilmektedir.

Political propaganda is communication and interaction activities aiming to influence the attitudes and behaviors of voters. Social media presents new opportunities for political propaganda in recent years, as it is an environment that allows for two-way communication and interaction. Twitter quantitatively contributes to the expansion of public debate by enabling community-recognized actors to reach broader masses. Also, it provides opportunity for anonymous users – who are not familiar with politics, newspaper writers and well-known bloggers – and marginalized voices to have influence on public debate. Thus social media differs from the traditional media in terms of providing opportunity for people, who could not raise their voice in the mainstream media, while publicizing their opinions about the debates on the agenda or even making an impact in a shorter time. In Turkey, there are politicians becoming more and more involved in social media and, besides, age of being elected was reduced to 18 years old. Therefore, it can be argued that social media would be one of the basic tools to be used for the purpose of political propaganda. The current study aimed to investigate to what extent social media was used by the candidates in presidential elections of Turkey. In our research model, while collecting and analyzing the data, a framework entitled as “Social media and political communication: a social media analytics framework” (Stieglitz & Dang-Xuan, 2013) was utilized to calculate individuals’ interaction rates and, to demonstrate how they used social media in terms of reciprocally interacting with voters. Official Twitter accounts of the candidates of the presidential election held on June 24, 2018 and their shares were analyzed using content analysis method. In total, more than two thousands of tweets of the candidates were analyzed using the NVivo 11.0 program. The survey covers the period from beginning of applications for Presidential candidacy (May 1, 2018) to June 28, 2018. Findings of the study showed that the Twitter usage strategy of the candidates focused on uni-directional sharing of information rather than two-way communication and interaction. In this respect, unlike the traditional media, no specific strategy was found except for the interactive e-rally. The sharing was largely shaped by the topics discussed in the traditional media, rallies and party meetings, and there was not significant effect of Twitter on context of the agenda setting. However, for users who followed the agenda from social media instead of traditional media, Twitter served as an important source of news about the issues that the public had talked about, and established the groundwork for debate reaching wider masses. Within the scope of propaganda activities; it was suggested that the candidates, who had less space for activities such as radio / television programs, rallies and open-air meetings due to different reasons, used Twitter more actively and interactively as an alternative channel to deliver their political messages to the voters. Candidates reached a high level of interaction over their followers as a result of their sharing which meant that they were able to transmit their messages to wider masses than their own voters. In this respect, it could be argued that although Twitter is not a form of direct voting, it may be an advantage for candidates in terms of gaining sympathy, reputation and perception management. Based on increasing Twitter usage and structure of demographic characteristics of Twitter users that represent Turkey, Twitter may be much more effective on both voting attitudes and behaviors in the elections to be held in the next years. Nowadays, social structures are shaped in parallel with technological developments, and communication tools have been undergoing structural changes in the face of these developments. On the one hand, as the number of younger candidates and voters who use technology has been increasing and the primary source of information for the “digital native” generation is social media such as Google, Youtube, Facebook and Twitter obviously, social media has potential to become a much more effective tool for the political sphere and participatory democracy in the next years. On the other hand, we cannot claim that social media would be in a totally different situation than the traditional media in the future due to the fact that it is under control of authorities. In other words, we would be somewhere between utopian point of view that social media may be more supportive of polyphony and a dystopic viewpoint which states that for authorities (not only states but also multinational corporations), it can be a facilitator of the process of routing and controlling society by the help of their technological features.
POLITICAL PROPAGANDA THROUGH SOCIAL MEDIA IN TURKEY: 2018 PRESIDENT ELECTION CASE